Presence of microorganisms in hemolymph of the horseshoe crab Limulus polyphemus. - Brandin, E R (1985)
Hemolymph samples obtained from Limulus polyphemus at the time of collection and after a 1-week holding period exhibited a significant increase in bacterial levels. No differences were observed in the ability of amoebocyte lysate, prepared from these same samples, to gel in the presence of lipopolysaccharide.